Operant conditioning in the bat Phyllostomus hastatus - Beecher, M. D. (1971)
Bats of the species Phyllostomus hastatus were trained to press a pigeon key with food as the reinforcer. Patterns of responding under fixed-ratio, fixed-interval, and variable-interval schedules of reinforcement were similar to those typically shown by other species. In a simple auditory discrimination, responding readily came under stimulus control. It is suggested that the behavioral method could be applied to various problem areas of bat behavior.